Two glacial mound fields in northern Savo Finland - Toive Aartolahti (Fennia: International Journal of Geography, 1975)
Two mound fields in central Finland contain numbers of large glacial drift mounds, circular in plan and conical in profile. Those belonging to the first field, which are composed mainly of stratified glaciofluvial material with layers of flow till, are interpreted as kames. Those of the second field are chiefly till but also contain some layers of fine glaciofluvial material. Some of these are explained as being thermokarst features formed by supraglacial material accumulating in sinkholes in the stagnant ice, and some as dead‑ice hummocky moraines and crevasse fillings. The structural and morphological features suggest that the till and glaciofluvial material were deposited in the same environment. The large quantities of supraglacial ablation till and flow till are of importance in the processes of deposition in both mound fields. The differences between the fields in the structure and morphology of the mounds are attributed to differences in location with respect to the level of the highest shore‑line and the resulting differences in conditions of deposition. Both fields are situated in a zone where a large amount of consistently fine supraglacial material accumulated as a result of a local retardation in the retreat of the ice sheet.